1979
DOI: 10.1111/j.1440-1681.1979.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sympathetic Innervation of the Mammalian Ovary. A Review of Pharmacological and Histological Studies

Abstract: The a i m of this article is to review the literature concerning the nature and function of the sympathetic innervation of the mammalian ovary. We focus our attention upon evidence relating to suggestions that ovarian smooth muscle participates in ovulatory events, and that such participation may be modulated by the local neural supply. Guttmacher & Guttmacher (1921) mentioned that this possibility was first suggested nearly 70 years before they observed smooth muscle-like cells in the follicular walls of sow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 96 publications
(93 reference statements)
0
14
1
Order By: Relevance
“…It has not been clearly established whether the ovarian sympathetic nerves play any role in the process of ovulation (Bahr, Kao & Nalbandov, 1974; Mohsin & Pennefather, 1979). Early studies involving abdominal sympathectomy (Sweet & Thorp, 1929;Brooks, 1935) suggested that the ovarian sympathetic nerves were not required for ovulation but results from more recent studies seem inconsistent with these findings.…”
Section: Introductioncontrasting
confidence: 46%
“…It has not been clearly established whether the ovarian sympathetic nerves play any role in the process of ovulation (Bahr, Kao & Nalbandov, 1974; Mohsin & Pennefather, 1979). Early studies involving abdominal sympathectomy (Sweet & Thorp, 1929;Brooks, 1935) suggested that the ovarian sympathetic nerves were not required for ovulation but results from more recent studies seem inconsistent with these findings.…”
Section: Introductioncontrasting
confidence: 46%
“…It is commonly assumed that catecholamines reach the ovary exclusively via its extrinsic sympathetic innervation (12). However, ovarian denervation reduces, but does not eliminate, the content of NE in the gland (13), implying the existence of an additional source of catecholamine synthesis.…”
mentioning
confidence: 99%
“…In vitro contractile experiments have been carried out in various vertebrate species, mainly in eutherian mammals [1][2][3][4]. Most of these experiments have been used to investigate the effects of different metabolic and pharmacological compounds on the contractility of the follicular wall.…”
Section: Discussionmentioning
confidence: 99%
“…The muscular apparatus of the ovary, mainly of the preovulatory follicle, has been investigated more thoroughly in eutherian mammals than in any other group of vertebrates [1][2][3][4]. Possible functions of the contractile apparatus of mammalian ovarian follicles include aid in follicular rupture [5], collapse of the follicular wall and corpus luteum formation [6], and compaction of the follicle during atresia [7].…”
Section: Introductionmentioning
confidence: 99%